Efficacy and safety of anagrelide as a first‐line drug in cytoreductive treatment‐naïve essential thrombocythemia patients in a real‐world setting. (17th June 2019) - Ito, Tomoki; Hashimoto, Yoshinori; Tanaka, Yasuhiro; Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Konishi, Akiko; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Hashimoto, Akiko; et al.
Abstract: Objective: This study aimed to retrospectively assess the efficacy and safety of anagrelide in cytoreduction therapy‐naïve essential thrombocythemia (ET) patients in a real‐world setting. Method: Data from 53 ET patients who received anagrelide as a first‐line therapy were reviewed for patient characteristics, antiplatelet status, cytoreduction status, therapeutic effects, adverse events, thrombohemorrhagic event development, progression to myelofibrosis or acute leukemia, and cause of death. Results: The rate of achieving a platelet count of <600 × 10 9 /L during anagrelide monotherapy was 83.0%. Adverse events occurred in 32 of 53 patients, and tended to be slightly more severe in patients with cardiac failure; however, they were mostly tolerable. The therapeutic effect of anagrelide was consistent, regardless of genetic mutation profiles. The incidence of anemia as an adverse event was significantly higher in the CALR mutation‐positive group. Favorable platelet counts were also achieved in patients for whom hydroxyurea was introduced as a replacement for anagrelide or in addition to anagrelide because of unresponsiveness or intolerance to treatment. Conclusion: In Japanese cytoreduction therapy‐naïve ET patients, anagrelide administration as a first‐line therapy demonstrated favorable effects in reducing platelet counts, and its safety profile that was generally consistent with those in previous reports.